Salt Marsh Synthesis: Local Politics, Local Identity Perception and Autonomy Initiatives on Canvey Island (Essex, UK) - Philip Hayward (Island Studies Journal, 2023)
Canvey Island, located on the north side of the Thames Estuary, has experienced periodic inundations since its earliest periods of settlement. The island was sparsely populated until the late 1800s when a series of developments, including the construction of fixed links to the mainland, attracted migrants from the East End of London who went on to form the core of the present-day population. The recent and relatively homogenous nature of this migration pattern has led to a local perception of difference from the more established communities of the adjacent Essex shore. The latter factor has contributed to a growing push for local autonomy on the island, which has connected with broader national political trends. The article identifies the manner in which experiences and perceptions of insularity can foster distinct senses of local difference and marginalisation that result in autonomy initiatives at grassroots levels. With regard to the latter, parallels are also drawn with previous local autonomy initiatives in the United Kingdom, particularly those of the Isle of Dogs in 1970. The article also emphasises the role of the imagination and representation of locality in promotional, popular cultural and political discourse that informs senses of community identity in various ways.